Asymptomatic Leishmania infection in humans: A systematic review - Milena Menezes Corrêa Pederiva; Sidney Mariano dos Santos; Liz Graciela Sanabria Rivarola; Victor Jorge Guerreiro; Katiana Simões Lopes; Manoel Sebastião da Costa Lima Junior; Herintha Coeto Neitzke-Abreu (Elsevier, 2023)
Background: Leishmaniasis is a highly prevalent neglected tropical disease. It mainly presents as two forms: cutaneous and visceral leishmaniasis, the latter being the most severe form. However, asymptomatic cases of Leishmania infection result in an increase in the underreporting and transmission of the protozoan Objectives: In this study, articles on the incidence of asymptomatic Leishmania infection were systematically reviewed. Methods: The publications identified in the Medline/PubMed and Science Direct databases included 4568 articles. Inclusion, exclusion, and eligibility criterion analysis resulted in 83 articles being retained. These studies were mostly performed in Brazil (n = 26) and India (n = 15). Results: Several detection techniques have been used for diagnosis. Among the species found were L. infantum and L. donovani, which result in visceral leishmaniasis, and L. amazonensis, L. braziliensis, and L. panamensis. The incidence rates varied between the analyzed locations, largely due to sampling and the presence or absence of endemism in the regions. The largest populations analyzed were in two studies performed in India and Nepal. One of these studies evaluated 32,529 people and the incidence rate was 8.3% (n = 2702), while the other study evaluated 21,267 people and the incidence rate was 1.76% (n = 375). Only 14.28% of the studies investigated leishmaniasis in blood donors. Preexisting diseases have also been reported. Conclusion: The findings of this systematic review present the incidence of cases of asymptomatic Leishmania infection worldwide, in addition to detailing the studies and offering information for researchers and health authorities to seek alternatives to reduce the number of leishmaniasis cases.